Multi-scale characterisation of a ferroelectric polymer reveals the emergence of a morphological phase transition driven by temperature - Jonas Hafner (Nature Portfolio, 2021)
Ferroelectric polymeric materials possess intermixture of crystalline and amorphous regions with complex Curie transition. Here, the authors demonstrate that the semi-crystalline morphology of the ferroelectric copolymer of P(VDF-TrFE) strongly affects its Curie transition.